Not all Natural Disasters are Covered Equal: A Focus on Canadian Media - Mamuji, Aaida; Kchouk, Bilel (Revue Gouvernance / Governance Review)

(untitled) (Centre d’études en gouvernance de l’Université d’Ottawa, 2017)
When Canada launches a Matching Fund in response to natural disasters abroad, the federal government commits to match dollar-for-dollar donations made by the Canadian public to eligible charities participating in disaster-relief efforts. In this study, we used both quantitative and qualitative research methods to analyze Canadian news coverage in response to these humanitarian crises. We found that there was variance in media coverage depending on the nature of the natural disasters, namely whether the disasters were sudden-onset or slow-onset. Sudden-onset disasters not only benefited from more television airtime and print media, the content of coverage was characteristically different than slow-onset disasters.